Whole-Body Vibration as a Warm-up Before Exercise-Induced Muscle Damage on Symptoms of Delayed-Onset Muscle Soreness in Trained Subjects - Magoffin, Ryan D; Parcell, Allen C; Hyldahl, Robert D; Fellingham, Gilbert W; Hopkins, J Tyson; Feland, J Brent (Journal of strength and conditioning research, 2020)
Magoffin, RD, Parcell, AC, Hyldahl, RD, Fellingham, GW, Hopkins, JT, and Feland, JB. Whole-body vibration as a warm-up before exercise-induced muscle damage on symptoms of delayed-onset muscle soreness in trained subjects. J Strength Cond Res 34(4): 1123-1132, 2020-There is no clear scientific evidence that whole-body vibration (WBV) used as a warm-up before performing eccentric exercise mitigates delayed-onset muscle soreness (DOMS) and speeds strength loss recovery. These benefits were observed primarily in nonresistance-trained individuals. The aim of this study was to determine whether WBV could mitigate soreness and expedite strength recovery for resistance-trained individuals when used as a warm-up before eccentric exercise. Thirty resistance-trained males completed 300 maximal eccentric contractions of the quadriceps after warming up with (WBV) or without (CON) WBV. Both CON and WBV experienced significant isometric (26.3 and 30.2%, respectively) and dynamic (50.9 and 46.4%, respectively) strength loss immediately after exercise. Isometric strength was significantly depressed after 24 hours in the CON group (8.2% p < 0.02), but not in the WBV group (5.9% p = 0.7). Isometric strength was no longer significantly depressed after 48 hours in the CON group (6.1% p < 0.07) or the WBV group (4.1% p = 0.20). Dynamic strength was significantly decreased in both the CON and WBV groups at 24 hours (17.7% p < 0.001 and 15.5% p < 0.001, respectively) and 48 hours (17.1% p < 0.01 and 13.6% p < 0.002), but only significant for the CON at 1 week after exercise (8.6% p = 0.05). Pain as measured by a visual analog scale was significant in both groups at 24 and 48 hours after exercise, but WBV experienced significantly less soreness than the CON group after 24 hours (28 vs. 46 mm p < 0.01, respectively) and 48 hours (38 vs. 50 mm p < 0.01). Pain pressure threshold increased significantly in both groups, but there was no difference between groups. These results suggest the use of WBV before eccentric exercise mildly mitigates DOMS in trained individuals. Application of WBV can function as a quick mode of warm-up before resistance training and can decrease pain perception from DOMS. This may be beneficial to athletes undergoing a heavy strength training phase where DOMS is likely.